PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MIND MAPPING UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS VIII F SMP NEGERI 15 YOGYAKARTA - Bernadetha Adityaningrum; A. A Sujadi (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this research was to describe the type cooperative learning mind mapping in improving the interest and learning achievement math of class VIII F SMP Negeri 15 Yogyakarta. The type of this research is a classroom action research. Subject in this study were students of class VIII F SMP Negeri 15 Yogyakarta, there are 34 students. The objective of this research is the interest and learning achievement using cooperative learning in mind mapping model. The results of this research showed that after application of the learning model, the interest and learning achievement were increased. The percentage of students interestÂ in the first cycle in the mount of 70.18% to 80.76% in the second cycle. The studentsâ€™ math learning achievement also be increased can be seen of the average percentage of the initial capabilities of students in the first cycle 63,02 to 72,73 and the second cycle of the percentage becomes 78.71. Thus, advised teachers to implement cooperative learning model of mind mapping to improveÂ the interest and learning achievement.